2020
DOI: 10.3390/life10120326
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Three RG(S/T)GR Pentapeptide-Containing Negative Regulators of HetR Results in Lethal Differentiation of Anabaena PCC 7120

Abstract: The filamentous cyanobacterium Anabaena sp. PCC 7120 produces, during the differentiation of heterocysts, a short peptide PatS and a protein HetN, both containing an RGSGR pentapeptide essential for activity. Both act on the master regulator HetR to guide heterocyst pattern formation by controlling the binding of HetR to DNA and its turnover. A third small protein, PatX, with an RG(S/T)GR motif is present in all HetR-containing cyanobacteria. In a nitrogen-depleted medium, inactivation of patX does not produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 65 publications
5
12
0
Order By: Relevance
“…Unlike contiguous heterocysts observed in patS mutant, or hetR overexpression strains, these heterocyst doublets have an abnormal neck connecting them. They appear to be at the different stages of cell constriction, which resemble those found in the polA mutant caused by incomplete DNA segregation and consequently failure of septum closure, or those reported for a conditional patS patX hetN tripple mutant ( Khudyakov et al, 2020 ). These heterocyst doublets are likely the results of delayed cell division, with persistent PG synthesis at the division site.…”
Section: Discussionsupporting
confidence: 61%
“…Unlike contiguous heterocysts observed in patS mutant, or hetR overexpression strains, these heterocyst doublets have an abnormal neck connecting them. They appear to be at the different stages of cell constriction, which resemble those found in the polA mutant caused by incomplete DNA segregation and consequently failure of septum closure, or those reported for a conditional patS patX hetN tripple mutant ( Khudyakov et al, 2020 ). These heterocyst doublets are likely the results of delayed cell division, with persistent PG synthesis at the division site.…”
Section: Discussionsupporting
confidence: 61%
“…This proposal includes the novel gene patX. This gene has recently been described as a redundant gene for the inhibitory mechanism of patS [19,20]. It has been also shown that, while its deletion in the wild-type background does not alter considerably the phenotype, the double mutant ∆patS patX is lethal with an almost complete Mch phenotype [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…This double mutant induces considerably more heterocysts than the single ∆patS mutant, S2. [20], with both slightly shorter vegetative intervals and a higher percentage of heterocysts. In Fig 3 we observe the agreement between the simulations and the experimental data from [54] for wild-type and patS and hetN mutants.…”
Section: Study Of the Wild-type And The ∆Pats And ∆Hetn Mutantsmentioning
confidence: 97%
See 1 more Smart Citation
“…In this Special Issue of Life on cyanobacterial cellular and molecular strategies for survival, we summarize some of the recent research advances in cyanobacterial biology in a wonderful collection of original research and review articles. By mutational studies, Khudyakov et al [ 1 ] investigated the influence of three small proteins (PatS, PatX and HetN) on HetR, the master regulator of heterocyst differentiation in the multicellular cyanobacterium Nostoc sp. PCC 7120.…”
mentioning
confidence: 99%